IMPLEMENTATION OF PRIMARY HEALTH CARE SYSTEM IN COUNTRIES - Memo Lukito; Ascobat Gani (Jurnal Administrasi Kesehatan Indonesia)
Background: Primary Health Care (PHC) systems are essential for delivering comprehensive and accessible health services globally, focusing on individuals’ and communities’ fundamental health and well-being.